Restructuring Health Education Materials to Improve Sexual and Reproductive Health Literacy among in School Adolescents - Nkrumah, J. (University of Ghana, 2024)
Adolescent sexual and reproductive health presents enormous public health problems in Sub Saharan Africa. The last few decades have witnessed increased teen pregnancy, HIV prevalence and other sexually transmitted infections, and low uptake of contraceptives. For instance, Ghana has a high teen pregnancy record, even among adolescents aged 10-14. National-level data shows that the Central Region came third among regions with high teen pregnancy prevalence. For example, in the Effutu-Municipality, most basic school adolescents are already in sexual relationships, making access to sexual and reproductive health information and education for adolescent critical in improving outcomes in the region. Access to information, education, and literacy is a sure antidote for reversing adverse outcomes. However, there is a paucity of literature in these areas. While Ghana’s adolescent sexual and reproductive health policies emphasize access to comprehensive quality services, information, and education to improve knowledge, there are inconsistencies between policy objectives and actions. National and sub-national assessments of the availability and accessibility of sexual and reproductive health information and education are scarce, making it difficult to appreciate the policies’ impact. Assessing adolescents’ sexual and reproductive health literacy needs is essential for providing critical feedback to policy-makers on the effectiveness of existing policies and identifying implementational gaps. For instance, adolescents in the Effutu Municipality have limited access to appropriate sexual and reproductive health information. The municipality has no adolescent corners or clubs in schools for sexual and reproductive health education. The situation in the Effutu-Municipality could reflect the national situation, making literacy needs assessment critical for revising existing interventions. This study improves adolescent sexual and reproductive health literacy and related outcomes by assessing adolescents’ sexual and reproductive health literacy needs and restructuring existing texts based on the assessment results. The study further assessed the effectiveness of the restructured texts in improving the sexual and reproductive health literacy of young adolescents. The study used a quasi-experimental and participatory action research designs. The study population included all in-school adolescents aged 11-15 living in the Effutu Municipality. Probability and nonprobability sampling were used to select sub-municipalities, communities, schools, and young adolescents. The study was divided into three main phases to achieve the research objectives.
PhD. Health Policy and Management
Keywords: teen pregnancy; HIV; Effutu-Municipality